Agroforestry for Nutrient Cycling and Soil Health Improvement - Kumar, Dhiraj (Indian Journal of Agroforestry, 2024)
The agroforestry systems often considered as a solution to mitigate climate change and to combat soil degradation. The practice of agroforestry creates sustainable and diverse land use systems with improved productivity, profitability, healthy and resilient ecosystem. The inclusion of trees in agroforestry system leads to modify the ecological processes mainly due to addition of tree litters and decomposition processes that adds to nutrient availability for the crops and efficient nutrient cycling. Growing of trees in conjunction with crops or pastures believed to provide sufficient plant cover to restrict the soil erosion and deep and prolific root architecture enhance the nutrient cycling in soils. Moreover, the amount of nutrient release from the litter depends on the soil types, characteristics of species, soil biota, climatic variables, land use pattern and management practices. Further, the nutrient inputs in agroforestry systems plays important role for soil organic carbon (SOC) sequestration and thus creates co-benefits for climate change mitigation and agricultural production. In addition, tree roots translocates the nutrients deep into the soil layer beyond the reach of annual crops or pastures. Thus, it is quite pertinent to know or to gain more knowledge as to how agroforestry system in varying complexity perform in diverse habitat and perform nutrient cycling that in turn influence the biomass production and making the nutrients available to the soil.